2009
DOI: 10.1074/jbc.m109.022244
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Family Negatively Regulates Hepatic Gluconeogenesis via Induction of Orphan Nuclear Receptor Small Heterodimer Partner in Primary Hepatocytes

Abstract: Hepatic gluconeogenesis is tightly balanced by opposing stimulatory (glucagon) and inhibitory (insulin) signaling pathways. Hepatocyte growth factor (HGF) is a pleiotropic growth factor that mediates diverse biological processes. In this study, we investigated the effect of HGF and its family member, macrophage-stimulating factor (MSP), on hepatic gluconeogenesis in primary hepatocytes. HGF and MSP significantly repressed expression of the key hepatic gluconeogenic enzyme genes, phosphoenolpyruvate carboxykina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 40 publications
4
70
0
Order By: Relevance
“…USFs are known to be engaged in several processes related to maintaining lipid and glucose homeostasis (43)(44)(45)(46). Thus, the role of USFs in the generation of the Th17 immune response is of potential interest for further understanding the proposed relationship between metabolic disorders and inflammation (47).…”
Section: Discussionmentioning
confidence: 99%
“…USFs are known to be engaged in several processes related to maintaining lipid and glucose homeostasis (43)(44)(45)(46). Thus, the role of USFs in the generation of the Th17 immune response is of potential interest for further understanding the proposed relationship between metabolic disorders and inflammation (47).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that AMPK elevated SHP gene expression via USF-1 (upstream stimulatory factor) (29). AMPK-mediated FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…The pGL3basic-G6Pase (Ϫ1227/ϩ57) and PEPCK (Ϫ2.0 kb) promoter constructs were previously described (29). 8ϫ CREluc constructs were constructed by inserting into the pGL2-promoter vector between BglII sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Moreover, the authors provide data indicating that TLR signaling induces endogenous SHP expression in an AMPKdependent manner, consistent with previous findings that show that AMPK contributes to the induction of shp expression by various extracellular stimuli. 8,9 TLRdependent activation of AMPK requires intracellular Ca 21 influx, whereas other extracellular stimuli might trigger AMPK activation in a Ca 21 -independent manner. AMPK activation mediates SHP expression via transcription factor upstream stimulatory factor-1.…”
mentioning
confidence: 99%